CONTENT MARKETING, ONLINE ADVERTISING, DAN PAYLATER TERHADAP IMPULSIVE BUYING PRODUK UMKM GO-DIGITAL PADA GENERASI Z DI WILAYAH DKI JAKARTA - Lola Tri Prihatini (2022)
MSMEs have been negatively affected on the sales side due to the Covid-19 pandemic, so they are trying to adapt by onboard to digital platforms. This study aims to determine the effect of marketing content, online advertising, and paylater on the impulsive buying of go-digital MSME products in generation Z in the DKI Jakarta area. This study used a quantitative descriptive analysis method. Then the data were obtained from distributing questionnaires using a non-probability sampling method with purposive sampling. So that the samples used were 167 generation Z consumers of MSME products who are domiciled in DKI Jakarta. Data analysis used is descriptive and inferential data analysis techniques using Partial Least Square (PLS) with SmartPLS 3.2.9 software. The results of this study indicate (1) Content marketing has a positive and significant influence on impulsive purchases with a path coefficient of 0.542. (2) Online advertising has no significant effect on impulse buying with a path coefficient of -0.127. (3) Paylater has a positive and significant influence on impulse purchases with a path coefficient of 0.428.advertising online, and paylater contribute 64.50% in influencing impulse buying, while the remaining 34.80% is influenced by other variables.